Animal and Clinical Studies Evaluating Blood Glucose Control With Palatinose-Based Alternative Sweeteners - Jang, Jaehyi; Jo, Kyungae; Hong, Ki-Bae; Jung, Eun Young (Frontiers in Nutrition, 2020)
Animal and clinical studies were performed to determine whether Palatinose-based alternative sweeteners with increased sweetness contributed to blood glucose elevations. In the animal study, male Sprague-Dawley rats (6 weeks old) received an oral load of 2 g of glucose or Palatinose-based alternative sweeteners per kilogram of body weight. Thirty minutes after the glucose load, the rat blood glucose levels in the Palatinose-based alternative sweetener groups were significantly lower than those in the glucose groups (p < 0.05). Palatinose-based alternative sweeteners significantly improved glucose tolerance in rats. However, significant differences in the blood glucose levels were not observed among the Palatinose-based alternative sweeteners. In the clinical study, 14 healthy volunteers (21.4±1.3 years) consumed glucose or Palatinose-based alternative sweeteners (50 g). At 60 min, when Palatinose-based alternative sweeteners were ingested, blood glucose was significantly lower compared to when glucose was ingested (Palatinose-L, 123.1 mg/dL; Palatinose-IS, 125.9 mg/dL; Palatinose-FOS. 129.1 mg/dL vs. glucose, 154.8 mg/dL, p < 0.05). The glycaemic index of Palatinose-L, Palatinose-IS and Palatinose-FOS was 43.9, 58.1 and 49.2, respectively. Palatinose-based alternative sweeteners could help maintain health as the postprandial blood glucose levels are constantly maintained owing to slow hydrolysis.